The association of pericardial fat and peri-aortic fat with severity of nonalcoholic fatty liver disease - Lee, Chun-Wei; Yun, Chun-Ho; Huang, Wen-Hung; Hung, Ta-Chuan; Tsai, Cheng-Ting; Kuo, Jen-Yuan; Su, Cheng-Huang; Cheng, Han-En; Hung, Chung-Lieh; Hou, Charles Jia-Yin (Scientific reports, 2022)
Visceral adipose tissue (VAT) is associated with central obesity, insulin resistance and metabolic syndrome. However, the association of body-site specific adiposity and non-alcoholic fatty liver disease (NAFLD) has not been well characterized. We studies 704 consecutive subjects who underwent annual health survey in Taiwan. All subjects have been divided into three groups including normal (341), mild (227) and moderate and severe (136) NAFLD according to ultrasound finding. Pericardial (PCF) and thoracic peri-aortic adipose tissue (TAT) burden was assessed using a non-contrast 16-slice multi-detector computed tomography (MDCT) dataset with off-line measurement (Aquarius 3DWorkstation, TeraRecon, SanMateo, CA, USA). We explored the relationship between PCF/TAT, NAFLD and cardiometabolic risk profiles. Patients with moderate and mild NAFLD have greater volume of PCF (100.7 ± 26.3vs. 77.1 ± 21.3 vs. 61.7 ± 21.6 ml, P < 0.001) and TAT (11.2 ± 4.1 vs. 7.6 ± 2.6 vs. 5.5 ± 2.6 ml, P < 0.001) when compared to the normal groups. Both PCF and TAT remained independently associated with NAFLD after counting for age, sex, triglyceride, cholesterol and other cardiometabolic risk factors. In addition, both PCF and TAT provided incremental prediction value for NAFLD diagnosis. (AUROC: 0.85 and 0.87, 95%, confidence interval: 0.82–0.89 and 0.84–0.90). Both visceral adipose tissues strongly correlated with the severity of NAFLD. Compared to PCF, TAT is more tightly associated with NAFLD diagnosis in a large Asian population.